Small stem Exeter total hip replacement: clinical and radiological follow-up over a minimum of 2.5 years. - Sivananthan, S.; Arif, M.; Choon, D.S.K. (2003)
Due to the smaller size of Asian femora, the small stem Exeter implant is a very useful development. This study suggests that it will perform as well as its larger counterparts.